Solution-processed Ga–Cd–O thin-films with tunable bandgaps and their transistors. (24th July 2018) - Liang, Lingyan; Liang, Yu; Wu, Weihua; Song, Anran; Yu, Jingjing; Chang, Ting-Chang; Lan, Linfeng; Yao, Zhiqiang; Cao, Hongtao
Abstract: Ga–Cd–O (GCO) thin films with different Ga contents were fabricated based on a solution-processed method. The direct optical bandgap of GCO films is changed from 2.89 to 4.53 eV with the Ga-content from 30% to 100% and their relationship agrees well with a second-order equation. The Raman spectra of GCO are dominated by three main features: a relatively sharp peak at 260 cm −1 and two broad features at 405 and 949 cm −1, and their variations with the Ga-content are analyzed associated with their phonon mode assignment. Moreover, thin-film transistors using the GCO channels all exhibit n-type transistor characteristics and the evolution of their key electrical parameters with the Ga-content is well elucidated by the structural and morphological properties. A saturation field-effect mobility of 5.1 cm 2 V −1 s −1, on/off current ratio of 2.1 × 10 7, subthreshold slop of 0.83 V/dec, and threshold voltage of −6.8 V were achieved by the 50% Ga-content device.